Imports, supply chains, and firm productivity - Carol Newman; John Rand; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper explores the relationship between imports and firm productivity, focusing on imported intermediates. Using firm-level data on over 20,000 manufacturing firms in Viet Nam, we find evidence for competition-induced productivity gains from trade. We show that gains in intermediate sectors spill-over to downstream sectors such that firms using more inputs from import-intensive sectors experience higher productivity gains. The evidence indicates that the main source of spill-over is better quality, domestically produced inputs. Ignoring the gains from trade through this mechanism may significantly underestimate the impact of trade on productivity.
Keywords: F61; F63; F14; O12; O53; 330; imports; supply chains; productivity; Viet Nam